Field shaper-based solutions to the bulging problem in magnetic pulse spot welding of dissimilar metal plates - Hang Zhang; Xiaoxiang Li; Quanliang Cao; Hongfa Ding (Scientific Reports)
Abstract Magnetic pulse spot welding based on a field shaper can effectively achieve spot welding of dissimilar metal plates by using the multi-turn flat coil and magnetic gathering through the field shaper. Through existing experimental research, it has been found that when using this method for welding, there will be a serious bulging problem in the center of the welding area, which will affect the flatness and aesthetics of the welding area, thereby affecting its application range. To solve this problem, this work proposes two different welding methods for welding dissimilar AA1060 aluminum and SS304 steel plates with a thickness of 1 mm: one based on the center opening of the flying plate and the other based on the pre-deformation of the flying plate. The causes of bulging and the effects of discharge voltage, welding gap, and inner hole radius of the field shaper on bulging size were studied. The cross-sectional morphology and mechanical properties of welded joints obtained by two welding methods were studied through numerical simulation, cross-sectional analysis, and tensile testing. The results indicated that both welding methods can successfully eliminate the bulging problem, and the point welding method based on the center opening of the aluminum plate can also reduce the minimum welding energy required for effective welding and improve welding efficiency. In addition, microscopic analysis results showed that a waveform composite interface was formed at the welding interface of the joint, and the connection performance of the welded joint was good. These two welding methods can also be extended to the welding of other dissimilar metal plates, which is of great significance for the industrial application of magnetic pulse spot welding technology based on field shaper.